2006
DOI: 10.1017/s0890060406060252
|View full text |Cite
|
Sign up to set email alerts
|

A constraint-based approach to feasibility assessment in preliminary design

Abstract: In this paper, we present the development and application of a technical feasibility model used in preliminary design to determine whether a set of desired product specifications obtained from marketing is feasible in the engineering domain. This model is developed by integrating the capabilities of a multiobjective design problem, a multicriteria design optimization tool, a Pareto frontier gap analyzer, metamodeling methods, and use of the Pareto frontier as a constraint for feasibility assessment. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Gurnani et al . (Gurnani et al ., ) have developed meta‐modelling techniques along with Pareto frontier gap‐analyzer method for characterization of the Pareto frontier for assessing achievability of performance targets. Ferguson et al .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Gurnani et al . (Gurnani et al ., ) have developed meta‐modelling techniques along with Pareto frontier gap‐analyzer method for characterization of the Pareto frontier for assessing achievability of performance targets. Ferguson et al .…”
Section: Introductionmentioning
confidence: 84%
“…Previous research works in this area can be found in (Gurnani et al ., ) and (Ferguson et al ., ). Gurnani et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If certain conditions are not met, then no further function evaluations take place. This type of strategy is used in conjunction with an optimization framework by Paredis [36], and by Gurnani et al [16,17].…”
Section: Approximation and Surrogate-based Approachesmentioning
confidence: 99%
“…Whether exploring a multiobjective performance space or a multidimensional tradespace, a designer must make a final selection from an often large number of alternatives. In multiobjective optimization problems, a designer must navigate the tradeoffs between competing objectives [1][2][3] and select the location on the Pareto frontier that best satisfies the preference structure of the designer. Similarly, tradespace analysis involves executing broad trade studies to understand which designs meet minimum requirements while locating those designs that best meet the goal of the project [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%